2014
DOI: 10.5194/angeo-32-519-2014
|View full text |Cite
|
Sign up to set email alerts
|

Planetary wave seasonality from meteor wind measurements at 7.4° S and 22.7° S

Abstract: Abstract. In this study we have used wind observation data from the mesosphere and lower thermosphere (MLT) region, obtained from meteor radar measurements in São João do Cariri . From the spectral analysis it was possible to identify the presence of planetary-scale oscillations in the hourly winds for the two latitudes and to study their transient character, which allowed elaboration of a climatology of planetary oscillation signatures. Planetary waves with periods near 2-days, 6-7 days, and 16 days were focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…At low latitudes, the Q16DW does not show significant seasonal variability (e.g., Lima et al, 2006; Araújo et al, 2014). Using neutral wind measurements obtained from two meteor radar stations at São João do Cariri (7.4°S, 36.5°W) and Cachoeira Paulista (22.7°S, 45.0°W), Araújo et al (2014) found that the Q16DW wave was strong from spring to midsummer and weak from autumn to early winter at São João do Cariri, whereas it had no obvious seasonal variability at Cachoeira Paulista. Using temperature data obtained from the Aura Microwave Limb Sounder (MLS) from January 2005 to December 2008, McDonald et al (2011) reported that the Q16DWs with wavenumbers 1 and 2 dominated the other modes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…At low latitudes, the Q16DW does not show significant seasonal variability (e.g., Lima et al, 2006; Araújo et al, 2014). Using neutral wind measurements obtained from two meteor radar stations at São João do Cariri (7.4°S, 36.5°W) and Cachoeira Paulista (22.7°S, 45.0°W), Araújo et al (2014) found that the Q16DW wave was strong from spring to midsummer and weak from autumn to early winter at São João do Cariri, whereas it had no obvious seasonal variability at Cachoeira Paulista. Using temperature data obtained from the Aura Microwave Limb Sounder (MLS) from January 2005 to December 2008, McDonald et al (2011) reported that the Q16DWs with wavenumbers 1 and 2 dominated the other modes.…”
Section: Introductionmentioning
confidence: 98%
“…Most of the reports on the Q16DW are focused on the winter hemispheric in the middle and high latitudes (e.g., Williams and Avery, 1992; Espy et al, 1997; Jacobi et al, 1998a, b; Mitchell et al, 1999; Luo Y et al, 2000, 2002a, b; Jiang GY et al, 2005; Takahashi et al, 2013; John and Kumar, 2016; Huang CM et al, 2017). In the middle and high latitudes, the Q16DW is typically strong during winter and weak during summer, based on neutral wind measurements obtained by radar (e.g., Williams and Avery, 1992; Espy et al, 1997; Namboothiri et al, 2002; Manson et al, 2004; Araújo et al, 2014; Guharay et al, 2016). At low latitudes, the Q16DW does not show significant seasonal variability (e.g., Lima et al, 2006; Araújo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesopause temperatures evaluated are based on observations that have been taken from two meteor radars operating at low latitudes in the Southern Hemisphere; one of them is located at São João do Cariri (7.4°S, 36.5°W) and the other at Cachoeira Paulista (22.7°S, 45°W) in the Brazilian northeast and southeast regions, respectively, which already have been described (e.g., Araújo et al, ; Lima et al, ). Both systems are all‐sky interferometric meteor radars with one 3‐element transmitting and five 2‐element receiving Yagi antennas, operating at a frequency of 35.24 MHz, with pulse width of 13.3 μs, repetition rate of 2144 Hz, and peak power of 12 kW.…”
Section: Observationsmentioning
confidence: 99%
“…Recently, Araujo et al (2014) and Guharay et al (2014) have presented a comprehensive study on seasonality and variability in the planetary waves and long-period atmospheric oscillations observed over equatorial and low-latitude stations. In their study, they have used long-term meteor wind radar measurements over Sao Joao do Cariri (7.4°S, 36.5°W) and Cachoeira Paulista (22.7°S, 45.0°W) in the southern hemisphere.…”
Section: Introductionmentioning
confidence: 99%